Implementasi Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen Terhadap Bisnis Biro Travel - Panggabean, Herman Daud; Badriyah, Siti Malikhatun (Fakultas Syariah INSURI Ponorogo, 2023)
Transportation business activities are often used by many people, and more and more times there are conflicts between sellers and buyers regarding cooperation in travel agency transactions related to promotions that are carried out online but are not in accordance with reality. To find out the implementation of Law No. 8 of 1999 concerning Consumer Protection (UUPK) related to business. And to find out the factors that influence the effectiveness of UUPK. The research method, namely normative juridical. The research approach is quantitative, data analysis techniques are data reduction, data presentation, and conclusions. The results of the research, that UUPK and UU no. 11 of 2008 concerning electronic information and transactions (UUITE) so that consumers can freely give their opinions. come to the LPKSM office for consultation. If the consumer gives power of attorney to LPKSM, LPKSM then makes a power of attorney which is signed and approved by the LPKSM consumer, an action that is carried out first with family efforts. Factors that influence the effectiveness of UUPK namely; The government is less responsive to community developments in electronic transactions, there are no regulations that technically provide protection to consumers against online transactions, business actors and consumers do not understand their rights and obligations. The conclusion from this study, LPKSM as an extension of the government has been active but there are no policies that technically regulate and protect consumers in electronic transactions, the factors that influence the effectiveness of the UUPK are the government which is less responsive, ignorance of consumers and business actors regarding their rights and obligations.